KNOWLEDGE AND PRACTICE ON MEDICAL WASTE MANAGEMENT OF HEALTH STAFFS AT THE NATIONAL EYES HOSPITAL, IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: Medical waste (CTYT) is a waste generated during the operation of medical facilitiesincluding harmful medical waste, common medical waste and medical wastewater. Good medicalwaste management contributes to protection for health workers, patients, family of patients,community health and living environment.Objectives: Describe the knowledge and practice on medical waste management of medical staff atthe National Eye Hospital and analyze some related factors.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 323 health workers (NVYT), National Eye Hospitalthrough questionnaires and observation using checklists. The research results show that the knowledgeand practice on medical waste managemnet in the control of hospital-acquired infections of healthworkers is quite good.Conclusion: The rate of health workers with knowledge on medical waste managemnet reached70,3%. The rate of health workers with practices on medical waste managemnet reached over 70%.There are 4 factors related to knowledge on medical waste managemnet including: age, workingposition, working time and professional qualifications. Three factors related to practices on medicalwaste managemnet including: Gender, working position and time of training on infection control(p
Keywords: Medical waste managemnet, related factors, health workers.